(9×13×1711×5×4)8=
\( \left(\frac{11\times5\times4}{9\times13\times17}\right)^8= \)
\( \left(\frac{1}{2\times3\times4}\right)^{-2}= \)
\( \left(\frac{7\times13}{6\times10\times12}\right)^{-3}= \)
\( \left(\frac{1}{4\times6\times9}\right)^{-4}= \)
\( \left(\frac{1}{5\times6\times7}\right)^{-3}= \)
A+B son correctas
\( \left(\frac{3}{5\times8\times7}\right)^{-2}= \)
\( \left(\frac{4}{9\times7}\right)^{-3}= \)
\( \left(\frac{5\times11}{4\times7\times9}\right)^{-2}= \)
\( \left(\frac{5}{6\times9\times11}\right)^{-3}= \)
\( \)\( \left(\frac{5\times3}{8\times4\times2}\right)^{-5}= \)
a' + b' son correctas
\( \left(\frac{5\times8\times6}{21\times23\times19}\right)^{-2}= \)
\( \)\( \left(\frac{7\times11\times19}{3\times12\times15}\right)^{-4}= \)
\( \left(\frac{10\times3}{7\times9}\right)^{-4}= \)
\( \left(\frac{11\times9}{4}\right)^{-5}= \)
\( \left(\frac{3\times5\times7}{2\times4\times6}\right)^{-2}= \)
B+C son correctas
\( \left(\frac{3\times5\times7}{4\times8\times10}\right)^5= \)
\( \left(\frac{4\times7\times8}{5\times9\times11}\right)^{-3}= \)
\( \left(\frac{4\times8}{5\times17\times3}\right)^{-4}= \)
\( \left(\frac{3\times7}{5\times8}\right)^{-3}= \)
\( \)\( \left(\frac{6\times8}{2\times7}\right)^{-5}= \)
a'+b' son correctas
A'+C' son correctas